Isolation and Morphological Characterization of Fungal Isolates from Leachate of Namo Bintang Landfill, North Sumatra - Niken Simanjuntak; Erman Munir; Yurnaliza (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to isolate and characterize the morphological characteristics of fungal colonies obtained from leachate water at a landfill site. To obtain fungi from leachate water, the following steps were taken: Fungi were isolated using the pour plate method with Potato Dextrose Agar (PDA) medium; morphological characterization of fungi was performed macroscopically and microscopically. Macroscopically, by observing the shape, edges, texture, and color of the fungal colonies, and microscopically, by observing the shape of the hyphae and the presence of asexual spores. The results showed that seventeen fungal isolates were successfully isolated from the leachate of the Namo Bintang landfill with different morphologies. The macroscopic characteristics of the fungal colonies showed that 15 fungal isolates had round colonies, and the other two isolates (NKD 07 and NKT 14) had irregular colonies. The edges of the fungal colonies varied, ranging from flat, wavy, to serrated. The color of the fungal colonies was predominantly gray and green. The texture of the fungal colonies varied from powdery, hairy, smooth, to cotton-like. Microscopic characteristics of the fungi show that most fungal isolates have septate hyphae and varied conidia shapes, such as round, oval, crescent, and tubular. These findings indicate that the leachate from the Namo Bintang landfill contains diverse fungi with different colony morphological characteristics, making it possible to develop them as biological agents.